Pengaruh Indeks Plastisitas Tanah Terhadap Koefisien Konsolidasi Vertikal (Cv) Dan Horizontal (Ch) - Fauzan Hidayattullah; Ferry Fatnanta; M. Yusa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Soft soils have instability problems that cannot be tolerated, so when a construction is to be built, the soft soil has to go through several methods of soil repair. One of them is by giving a load above the ground to increase the pressure of pore water in the soil, so that the water that fills the pore space on the ground out so that it causes the volume of pores in the soil to shrink and is also followed by a settlement in soil, this event is called consolidation. Generally consolidation occurs only in the vertical direction (cv), while in this study horizontal direction consolidation (ch) was obtained by modifying the consolidation test by using a membrane to limit the movement of pore water when compressed by the load so that the water moves radially towards the vertical hole containing the sand that has been prepared. This study aims to analyze between vertical consolidation coefficient (cv) and horizontal consolidation coefficient (ch) which is associated with the physical properties of soil namely soil plasticity index through laboratory tests. Therefore, it is necessary to vary soil samples that have diverse physical properties of soil, soil sample variation is obtained by mixing two types of soils that have different soil classifications using weight percentages of 0%, 25%, 50%, 75% and 100%. The results of this study showed soil samples that had a high plasticity index resulted in a greater value of vertical consolidation coefficient (cv) and horizontal consolidation (ch) compared to soil samples that had low plasticity index values. It is also related to the consolidation testing method which has differences in flow length and physical properties of soil samples such as moisture content (w), type weight (Gs) and initial pore number (eo) which affect to time of settlement. Keywords : Soft, soil, Consolidation, Vertical drain, Physical properties, Atterberg limit, Plasticity Index